2013
DOI: 10.1111/tmi.12132
|View full text |Cite
|
Sign up to set email alerts
|

Village registers for vital registration in rural Malawi

Abstract: Paper-based village registers were introduced 5 years ago in Malawi as a tool to measure vital statistics of births and deaths at the population level. However, usage, completeness and accuracy of their content have never been formally evaluated. In Traditional Authority Mwambo, Zomba district, Malawi, we assessed 280 of the 325 village registers with respect to (i) characteristics of village headmen who used village registers, (ii) use and content of village registers, and (iii) whether village registers prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…If we do not take into account the CWs in our study, the number of live births not reported by any source rises from 18.2% to 26.8% in group 1 and from 18.3% to 23.3% in group 2. These results bear out the positive benefit of the CWs in improving the vital statistics system, as reported by studies in Malawi, Indonesia and in DRC [17][18][19]. The estimates made in group 1 are questionable as the optimum model seems to be the saturated model [23,31].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…If we do not take into account the CWs in our study, the number of live births not reported by any source rises from 18.2% to 26.8% in group 1 and from 18.3% to 23.3% in group 2. These results bear out the positive benefit of the CWs in improving the vital statistics system, as reported by studies in Malawi, Indonesia and in DRC [17][18][19]. The estimates made in group 1 are questionable as the optimum model seems to be the saturated model [23,31].…”
Section: Discussionmentioning
confidence: 74%
“…To improve the exhaustiveness of information concerning vital events, various strategies have been proposed and implemented at national level in countries such as Ghana and India, with varying degrees of success [6,8,16]. On a more local level, in Malawi, Indonesia and DRC, studies have identified positive experiences with community-based organisations [4,[17][18][19]. According to these studies, the workers of community-based organisations or community workers (CW) could represent an opportunity to improve the performance of RHIS as regards the exhaustiveness of vital events.…”
Section: Introductionmentioning
confidence: 99%
“…India [62], Malawi [52] Supply Integration of birth and/or death registration in existing services (e.g., health facilities or burial sites) was low cost, required minimal additional human or IT infrastructure, and reduced indirect costs for clients.…”
Section: Supplymentioning
confidence: 99%
“…Albania [75], Botswana [72], Brazil [71], Ghana [64], India [59,73], Malawi [52], Peru [56] Incentive Requiring a national ID for government services (e.g., education, social protection, voting, etc.) and subsequently linking birth registration to national ID provision improved human resource availability, physical infrastructure accessibility, and client uptake of birth registration.…”
Section: Supplymentioning
confidence: 99%
“…Infrastructure problems mean that neither paper death certificates nor computerized records are gathered reliably into a central vital registration system. By some estimates, three-quarters of Malawi's deaths are never officially reported [6]. Instead, maternal mortality is estimated from samples of Malawi residents who are surveyed about the lives and deaths of their adult siblings.…”
Section: Making Numbersmentioning
confidence: 99%